2013
DOI: 10.1371/journal.pone.0078161
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of α-L-Iduronidase Expression in Immunocompetent Mice Treated with the Sleeping Beauty Transposon System

Abstract: The Sleeping Beauty transposon system, a non-viral, integrating vector that can deliver the alpha-L-iduronidase-encoding gene, is efficient in correcting mucopolysaccharidosis type I in NOD/SCID mice. However, in previous studies we failed to attain reliable long-term alpha-L-iduronidase expression in immunocompetent mice. Here, we focused on achieving sustained high-level expression in immunocompetent C57BL/6 mice. In our standard liver-directed treatment we hydrodynamically infuse mice with plasmids containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…2. SB transposons for cSEAP expression and human (h)GUSB and hIDUA have been described previously, 13,18,19,41,45 as have plasmids for co-delivery of expression cassettes for SB transposases, pCMV-SB11, mini(m)Ub-SB11, 19,46 and pCMV-SB100X. 47 Liver-specific promoter (LSP) ApoEHCRhAAT 40 was a gift from Dr. Mark Kay (Stanford University, CA).…”
Section: Sb Vectorsmentioning
confidence: 99%
See 3 more Smart Citations
“…2. SB transposons for cSEAP expression and human (h)GUSB and hIDUA have been described previously, 13,18,19,41,45 as have plasmids for co-delivery of expression cassettes for SB transposases, pCMV-SB11, mini(m)Ub-SB11, 19,46 and pCMV-SB100X. 47 Liver-specific promoter (LSP) ApoEHCRhAAT 40 was a gift from Dr. Mark Kay (Stanford University, CA).…”
Section: Sb Vectorsmentioning
confidence: 99%
“…The SB transposon pKT2/ApoEHCRhAAT-cGUSB was engineered by inserting the full-length canine (c)GUSB into a unique EcoRI site of the pKT2-ApoE-hAAT-BGintron plasmid. 13 The plasmid containing cGUSB was a gift from Dr. Kathy Ponder (Washington University, St. Louis, MO). Prior to injection into dogs, plasmids were hydrodynamically infused into C57BL/6 mice to ensure transgene expression and transposition.…”
Section: Sb Vectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two approaches can even be combined[87].Recent progresses in genome editing technology using engineered zinc finger nucleases (ZFN), transcriptional activator-like effector nucleases (TALEN), and the clustered regularly interspaced short palindromic repeat (CRISPR) system have enabled the possibility of precisely modifying target sites in the genome without the use of viruses[88][89][90]. A recent study demonstrated that a transposable element (transposons) was able to integrate exogenous DNA into host cells, and showed benefits in MPS I mice[91,92]. Sangamo BioSciences Inc.(Richmond, CA, USA), is evaluating through a clinical trial (NCT02702115) the safety, the tolerability and the effect on plasma IDUA enzyme activity of ascending doses of SB-318.…”
mentioning
confidence: 99%